Candida albicans Fungaemia following Traumatic Urethral Catheterisation in a Paraplegic Patient with Diabetes Mellitus and Candiduria Treated by Caspofungin. (8th October 2013) - Vaidyanathan, Subramanian; Soni, Bakul; Hughes, Peter; Ramage, Gordon; Sherry, Leighann; Singh, Gurpreet; Mansour, Paul
Abstract : A 58-year-old paraplegic male, with long-term indwelling urethral catheter, developed catheter block. The catheter was changed, but blood-stained urine was drained intermittently. A long segment of the catheter was seen lying outside his penis, which indicated that the balloon of Foley catheter had been inflated in urethra. The misplaced catheter was removed and a new catheter was inserted correctly. Gentamicin 160 mg was given intravenously; meropenem 1 gram every eight hours was prescribed; antifungals were not given. Twenty hours later, this patient developed distension of abdomen, tachycardia, and hypotension; he was not arousable. Computed tomography of abdomen revealed inflamed uroepithelium of right renal pelvis and ureter, 4 mm lower ureteric calculus with gas in right ureter proximally, and vesical calculus containing gas in its matrix. Urine and blood culture yielded Candida albicans . Identical sensitivity pattern of both isolates suggested that the source of the bloodstream infection was most likely urine. Both isolates formed consistently high levels of biofilm formation in vitro as assessed using a biofilm biomass stain, and high levels of resistance to voriconazole were observed. Both amphotericin B and caspofungin showed good activity against the biofilms. HbA1c was 111 mmol/mol. This patient was prescribed human soluble insulin and caspofungin 70 mg followed by 50 mg daily intravenously. He recovered fully from candidemia.